1992
DOI: 10.1038/ki.1992.309
|View full text |Cite
|
Sign up to set email alerts
|

Long-term comparison between captopril and nifedipine in the progression of renal insufficiency

Abstract: To verify the hypothesis that angiotensin-converting enzyme (ACE) inhibitors possess a unique renoprotective effect in progressive chronic renal disease, we decided to compare the effects of an ACE inhibitor and a calcium antagonist on both hypertension and the progression of non-diabetic renal insufficiency in a long-term study. A four-year, multicenter, prospective, randomized trial was conducted on 142 hypertensive patients (pts) with established chronic renal failure from six Italian nephrology departments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
113
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(117 citation statements)
references
References 32 publications
3
113
1
Order By: Relevance
“…In this study, BP was remarkably reduced by nitrendipine, which might have accounted for its anti-albuminuric effect. This observation is consistent with previous reports that BP control is an important factor in reducing UAE in hypertensive patients with both incipient and overt nephropathy 3,5,24,41,42 ; and (b) second, the late effect of nitrendipine on UAE, which resembles our previous observation with another dihydropyridine CCB, amlodipine, 23 suggests that the duration of follow-up of intervention trials must be sufficiently long in order to fully detect the drug effect on UAE.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, BP was remarkably reduced by nitrendipine, which might have accounted for its anti-albuminuric effect. This observation is consistent with previous reports that BP control is an important factor in reducing UAE in hypertensive patients with both incipient and overt nephropathy 3,5,24,41,42 ; and (b) second, the late effect of nitrendipine on UAE, which resembles our previous observation with another dihydropyridine CCB, amlodipine, 23 suggests that the duration of follow-up of intervention trials must be sufficiently long in order to fully detect the drug effect on UAE.…”
Section: Discussionsupporting
confidence: 92%
“…The lack of a control group on placebo did not allow us to quantify how much the antihypertensive therapy with ramipril and nitrendipine slowed down the decline of renal function in our patients as compared to untreated patients. However, in our experience, the rates of decline found in both the ramipril and the nitrendipine groups were rather low at least in comparison to that previously reported by other authors 42,44 although the differences in the various study populations make it difficult to make such a comparison. These findings suggest that both drugs may exert a renoprotective effect with no difference between the ACE-I and the CCB.…”
Section: Discussioncontrasting
confidence: 69%
“…30 However, prospective clinical trials have revealed that calcium channel blockers are almost as effective as ACE inhibitors for preventing the progression of renal failure. 31 In fact, calcium channel blockers have demonstrated diverse effects on glomerular haemodynamics in spontaneously hypertensive rats. 32 The STONE study was a largescale clinical trial that demonstrated a decline in the incidence of cardiovascular events and stroke with nifedipine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Bianchi et al (7) have shown a close relationship between microalbuminuria and both morbidity in cardiovascular diseases and mortality in essential hypertension. Erley et al (8) (27) reported that there is only a slight difference between captopril and a calcium antagonist, nifedipine, in terms of BP reduction and protection against renal failure progression in hypertensive patients with renal insufficiency. Therefore, the present study was undertaken to evaluate the effects of an ACE inhibitor, lisinopril, and a calcium antagonist, nitrendipine, on UAE and renal function in mild to moderate essential hypertensive patients with microalbuminuria.…”
Section: Introductionmentioning
confidence: 99%